Pectoralis Major Musculocutaneous Flap and Splitthickness Skin Graft for The Reconstruction of Pharyngocutaneous Fistula After Total Laryngeal Resection - Atmodiwirjo, Parintosa; Pribadi, Sweety (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Pharyngocutaneous fistula (PCF) is the most frequent complication in the early postoperative period after total laryngectomy. Most PCF respond well to conservative management, but when it fails and the fistula persists surgical closure in indicated. Patients and Methods: Sixty-five year-old male was consulted to our division following total laryngectomy by the Ear Nose Throat surgeons, with wound dehiscence and pharyngocutaneous fistula. We performed a pectoralis major musculocutaneous flap (PMMCF) to close the fistula after a failed conservative management. The skin island of PMMCF was used as an inner lining to close the laryngeal fistula, the exteriorized muscle part of the